Zero Morph in Kurdish Language - Omar, Diman; Ahmed, Baez (Humanities Journal of University of Zakho, 2022)
Morph is one of the important Linguistic Subject that work like the morpheme in morphology, but it hasn't been discussed widely by linguists especially zero morph, In spite of the fact that it has an active role in morphology. Since first there are many items that became zero morph in language and the same in Kurdish language as one of International language? Second, the differences of linguists opinions about defining this term, whether the morph , morpheme, allomorph become zero morph, But after investigations according to ( Descriptive search)it become clear that it's the morph that becomes (zero) , not morpheme or allomorph beside the difference between it and the curtailment and cancelling items that are also known as Dissembling and anonymous items. This research attempt to clarify zero morph in Kurdish language, especially to clear up that the morph is the item that become zero. Then, to identify the domains that zero morph related with.